Elevation of preoperative serum hs-CRP is an independent risk factor for malnutrition in patients with gastric cancer - Yuantian Mao; Yuantian Mao; Yuantian Mao; Jinlu Liu; Jinlu Liu; Jiaming Li; Yue Qiu; Zhen Wang; Zhen Wang; Zhen Wang; Bopei Li; Bopei Li; et al. (Frontiers in Oncology, 2023)
BackgroundRecent studies have reported hypersensitive C-reactive protein (hs-CRP) linked to clinicopathological characteristics and nutritional status of the tumor, but its clinical significance in GC remains unclear. This study aimed to investigate the relationship between preoperative serum hs-CRP level and clinicopathological features and nutritional status in gastric cancer (GC) patients.MethodsThe clinical data of 628 GC patients who met the study criteria were analyzed retrospectively. The preoperative serum hs-CRP level was divided into two groups (<1 mg/L and ≥1 mg/L) to evaluate clinical indicators. Nutritional Risk Screening and nutritional assessment of GC patients were performed by the Nutritional Risk Screening 2002 (NRS2002) and the Patient-Generated Subjective Global Assessment (PG-SGA), respectively. The data were subjected to chi-square test, univariate and multivariate logistic regression analyses, respectively.ResultsThe analysis of 628 GC cases revealed that 338 patients (53.8%) were on malnutrition risk(NRS2002≥3 points), and 526(83.8%) had suspected/moderate to severe malnutrition(PG-SGA≥ 2 points). Preoperative serum hs-CRP level was significantly correlated with age, tumor maximum diameter (TMD), peripheral nerve invasion (PNI), lymph-vascular invasion (LVI), depth of tumor invasion (DTI), lymph node metastasis (LNM), pTNM stage, body weight loss (BWL), body mass index (BMI), NRS2002 score, PG-SGA grade, hemoglobin (HB), total protein (TP), albumin (ALB), prealbumin (PAB) and total lymphocyte count (TLC). Multivariate logistic regression analysis revealed that hs-CRP (OR=1.814, 95%CI=1.174-2.803; P=0.007), age, ALB, BMI, BWL and TMD were independent risk factors for existing malnutritional risk in GC. Similarly, non-malnutrition and suspected/moderate to severe malnutrition groups presented that hs-CRP (OR=3.346, 95%CI=1.833-6.122; P< 0.001), age, HB, ALB, BMI and BWL were independent risk factors for malnutrition in GC.ConclusionIn addition to the generally used nutritional evaluation indicators such as age, ALB, BMI, and BWL, the hs-CRP level may be used as a nutritional screening and evaluation indicator for GC patients.